Keperluan Prosedur Forensik Digital dalam Pembuktian Jenayah Siber di Mahkamah Syariah: Isu dan Cabaran/ The Need of Digital Forensics Procedure in Proving Cyber Criminal Offences in Malaysian Syariah Courts: Issues and Challenges (UMRAN - Journal of Islamic and Civilizational Studies, 2026)
The prosecution of cyber offences in Malaysian Syariah courts faces a procedural gap whereby the Syariah Court Evidence (Federal Territories) Act 1997 [Act 561] has yet to prescribe clear technical standards for the acquisition, analysis and presentation of digital evidence. This has resulted in the evaluation of digital evidence remaining dependent on judicial discretion in the absence of uniform forensic guidelines. This study analyses the need for digital forensic procedures in proving cyber criminal offences in Syariah courts by examining its foundations from technical, legal and Sharīʿah perspectives. Through doctrinal analysis and document analysis, the study examines Act 561 provisions, Practice Direction No. 4 of 2020, Islamic evidentiary principles and selected Syariah court cases involving digital evidence. Findings demonstrate that the provisions on al-kitābah, al-qarīnah and raʾy al-khabīr in Act 561 provide a principled basis for the reception of digital evidence, while Sharīʿah concepts such as maṣlahah, ʿurf and the tradition of inference- and expertise-based proof reinforce the necessity of digital forensics as a contemporary evidentiary method. However, these foundations remain unsupported by adequate technical procedures. Two principal issues are identified: a legislative-technical gap requiring clarification of the legal status of digital evidence and the expansion of Practice Direction No. 4 of 2020 into a more operationally detailed procedural guide and a human capital deficit in digital forensic literacy encompassing Syariah judges, prosecutors, religious enforcement officers and forensic experts. This study advances a technical, legal and Sharīʿah-based justification for the development of standardised digital forensic procedures in Malaysian Syariah courts, thereby contributing to the discourse on reforming the Syariah evidentiary system in confronting the realities of contemporary digital crime.
Keywords: Digital forensics; digital evidence; Syariah cyber offences; Syariah court; evidentiary procedure.